Kesadaran Hukum Konsumen Atas Pembelian Produk Impor Kemasan Yang Tidak Mencantumkan Label Bahasa Indonesia - Dwisvimiar, Inge; Muslih, Muhammad; Lathifa, Gita Fitri (Indonesian Journal Publisher, 2024)
The surge in food imports has given rise to issues about the safety and consumer consciousness of imported food items without Indonesian labelling. The objective of the study is to examine the legal consciousness of customers at Ranch Market Tangerang with relation to packaged imported food items lacking Indonesian labels, and to elucidate the resolution process for imported food goods without Indonesian labels at Ranch Market. Conduct research using an empirical approach in the field of law. The technique is specifically applicable to concrete occurrences. The data sources consist of secondary data and primary data, which are collected using interview techniques and analysed using descriptive qualitative methods. The findings of this study indicate that the legal awareness of consumers at Ranch Market Tangerang regarding imported packaged products lacking Indonesian language labels is demonstrated through indicators of legal knowledge, comprehension, attitudes, and behaviour. Consequently, there is a necessity for enhancing consumer awareness across all indicators. The Food and Drug Supervisory Agency (BPOM) at Ranch Market handles the settlement of imported food products without Indonesian language labels. This is done through their supervisory function as the responsible party for resolving imported food products that have shown unsatisfactory results.